2020
DOI: 10.1016/j.diabres.2020.108297
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease (Covid-19): How does the exercise practice in active people with type 1 diabetes change? A preliminary survey

Abstract: Aims: Coronavirus disease (Covid-19) could lead persons with pre-existing medical conditions to severe respiratory infections. The Italian Government introduced quarantine to limit viral transmission. This measure could lead people with type 1 diabetes (PWT1D) to disrupt daily care routine including PA practice with difficulties in glycemia management.This study aims to explore PA level in PWT1D before and during quarantine and to describe variation in glycemia values.Methods: An online survey investigating me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 21 publications
3
52
1
7
Order By: Relevance
“…The beneficial effect of physical activity on glycosylated hemoglobin (HbA1c) has been extensively investigated and a meta-analysis showed an overall effect on HbA1c of -0.85% (14). Data we found in our children and adolescents disagree with that obtained in adults with T1D in which it was reported a decrease in exercise and a worst in glucose values (15,41). Again, glycemic control in adolescents with T1D using hybrid closed loop system did not worsen during the restrictions due to COVID-19 pandemic and further improved in those who continued physical activity during the first 2-week of quarantine, confirming the importance of maintaining a regular physical activity also at home (19).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The beneficial effect of physical activity on glycosylated hemoglobin (HbA1c) has been extensively investigated and a meta-analysis showed an overall effect on HbA1c of -0.85% (14). Data we found in our children and adolescents disagree with that obtained in adults with T1D in which it was reported a decrease in exercise and a worst in glucose values (15,41). Again, glycemic control in adolescents with T1D using hybrid closed loop system did not worsen during the restrictions due to COVID-19 pandemic and further improved in those who continued physical activity during the first 2-week of quarantine, confirming the importance of maintaining a regular physical activity also at home (19).…”
Section: Discussioncontrasting
confidence: 91%
“…However, due to the suspension of outside structured physical and leisure activities, housebound children and adolescents with T1D needed to change their disease care, so concerns about possible harmful effects on glycemic control were arisen (14). To the best of our knowledge, studies on how the change in daily activities and lifestyles during lockdown has affected glycemic control in subjects with T1D are few and have small samples or short observation times (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups from Italy, Spain and the UK have reported that patients with T1DM and without COVID-19 have shown no deteriorations in glycaemic control, and often even show improvements in control, during the pandemic compared with a control period before the pandemic 131 133 . During lockdown, self-reported physical activity was found to be reduced 133 , 134 and more consistent patterns of nutrient intake and sleep were found 133 ; these findings might reflect conditions under which glycaemic control is easier to achieve. This effect might differ from the situation in developing countries with reduced access to food, medications, blood glucose test strips and medical services 135 , 136 .…”
Section: Covid-19 and T1dmmentioning
confidence: 89%
“…To limit viral transmission, most governments introduced national quarantine reducing movements and social interaction with the imperative "stay at home." Lockdown is considered the extreme option to protect health and in particularly most vulnerable people (those aged ≥65 years, and those with pathologies such as chronic heart, lung kidney and liver diseases, diabetes, and obesity), but it caused considerable disruption to the routine of the general population (2,3). The closure of gyms, stadiums, pools, dance and fitness studios, physiotherapy centers, parks, playgrounds reduced the possibility to practice Physical Activity (PA) in outdoor setting and, in general, the exercise options (4,5).…”
mentioning
confidence: 99%